The chemical profiling and assessment of antioxidative, antidiabetic and antineurodegenerative potential of Kombucha fermented Camellia sinensis, Coffea arabica and Ganoderma lucidum extracts. Issue 1 (9th December 2022) - Pavlović, Mariana Oalđe; Stajić, Mirjana; Gašić, Uroš; Duletić-Laušević, Sonja; Ćilerdžić, Jasmina
Abstract : The scientific interest in the medicinal properties of Kombucha beverages, a carbonated drink with live microorganisms, has increased recently. Abstract : The scientific interest in the medicinal properties of Kombucha beverages, a carbonated drink with live microorganisms, has increased recently. Hence, the aim of this study was to determine the chemical profile and to examine the antioxidant, antidiabetic and antineurodegenerative potential of unfermented and also Kombucha fermented Camellia sinensis (green tea), Coffea arabica (coffee), and Ganoderma lucidum (Reishi) extracts. The extracts were prepared as follows: the first (unfermented) set contained 1 L of water, 50 g of sucrose and 20 g of dried and ground green tea, coffee, or Reishi basidiocarp, while the second (fermented) set contained all of the aforementioned ingredients individually inoculated with Kombucha and fermented for 21 days. The chemical analysis was conducted using liquid chromatography–mass spectrometry (LC-MS). The antioxidant activity was assessed by DPPH, total reducing power (TRP), and β-carotene bleaching assays. The inhibition of α-amylase and α-glucosidase activity was used to estimate the antidiabetic potential, while the level of inhibition of acetylcholinesterase (AChE) and tyrosinase (TYR) was used to evaluate the antineurodegenerative activity. The results suggested that the fermented extracts of green tea, coffee, and Reishi exert significant antioxidant effects, although they were lower compared to the unfermented extracts. The unfermented green tea extract exhibited the highest DPPH-scavenging activity (87.46%) and the highest preservation of β-carotene (92.41%), while the fermented coffee extract showed the highest TRP (120.14 mg AAE per g) at 10 mg mL −1 . Although the extracts did not inhibit the activity of α-amylase, they were quite effective at inhibiting α-glucosidase, especially the unfermented Reishi extract, inhibiting 95.16% (at a concentration of 10 mg mL −1 ) of α-glucosidase activity, which was slightly higher than the positive control at the same concentration. The most effective AChE inhibitor was unfermented green tea extract (68.51%), while the fermented coffee extract inhibited 34.66% of TYR activity at 10 mg mL −1 . Altogether, these results are in accordance with the differences found in the extracts' chemical composition. Finally, this is the first report that highlights the differences in the chemical profile between the unfermented and Kombucha fermented green tea, coffee and Reishi extracts, while it also reveals, for the first time, the antineurodegenerative potential of Kombucha fermented Reishi extract. The examined extracts represent potent functional foods, while their more detailed mechanisms of action are expected to be revealed in future research.